(untitled) - Abdul-Jabbar, Kareem; 1947-; Obstfeld, Raymond; 1952- (New York, 2013)
Eighth-grader Theo Rollins' growth spurt has Coach Mandrake trying to transform him into a basketball star, but training time is hurting the science club's chances of winning the "Aca-lympics," and being accused of stealing could mean Theo is off both teams.
Keywords: African Americans; Fiction; Interpersonal relations; Basketball; Science clubs; Fiction; Fiction; Fiction; Jews; United States; Mystery and detective stories; JUVENILE FICTION / Sports & Recreation / Basketball; JUVENILE FICTION / Mysteries & Detective Stories; JUVENILE FICTION / Social Issues / Friendship; Fiction; Fiction; Schools; Fiction; Middle schools; Juvenile fiction; Juvenile fiction; Basketball; Juvenile fiction; Schools; Juvenile fiction; Interpersonal relations; Science clubs; African Americans; Juvenile fiction; Jews; Juvenile fiction; United States; Detective and mystery stories; Middle schools; Juvenile fiction